2016
DOI: 10.1371/journal.ppat.1005635
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Structure and Biochemical Characterization of an RNA Endonuclease in the N Terminus of Andes Virus L Protein

Abstract: Andes virus (ANDV) is a human-pathogenic hantavirus. Hantaviruses presumably initiate their mRNA synthesis by using cap structures derived from host cell mRNAs, a mechanism called cap-snatching. A signature for a cap-snatching endonuclease is present in the N terminus of hantavirus L proteins. In this study, we aimed to solve the atomic structure of the ANDV endonuclease and characterize its biochemical features. However, the wild-type protein was refractory to expression in Escherichia coli, presumably due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 58 publications
0
46
0
Order By: Relevance
“…Here, we report the identification of the N-terminal endonuclease domain of the L polymerase of SFTSV, which is crucial for cap-dependent viral mRNA transcription. We solved the X-ray crystal structure of the endonuclease domain at 2.4-Å resolution, which revealed features that are unique to SFTSV as well as those features that are shared among other cap-snatching viral endonuclease domains (Ferná ndez-García et al, 2016;Jones et al, 2019;Reguera et al, 2010Reguera et al, , 2016Song et al, 2016). We also demonstrated the inhibition of SFTSV and HRTV endonuclease activities by using IAV polymerase acidic protein (PA) inhibitors, including Baloxavir acid (BXA) derived from a recently FDA-approved drug, Baloxavir marboxil (BXM), suggesting that the banyangvirus endonuclease domain is a major therapeutic target that can guide the development of broad-spectrum antivirals against sNSVs.…”
Section: In Briefmentioning
confidence: 99%
“…Here, we report the identification of the N-terminal endonuclease domain of the L polymerase of SFTSV, which is crucial for cap-dependent viral mRNA transcription. We solved the X-ray crystal structure of the endonuclease domain at 2.4-Å resolution, which revealed features that are unique to SFTSV as well as those features that are shared among other cap-snatching viral endonuclease domains (Ferná ndez-García et al, 2016;Jones et al, 2019;Reguera et al, 2010Reguera et al, , 2016Song et al, 2016). We also demonstrated the inhibition of SFTSV and HRTV endonuclease activities by using IAV polymerase acidic protein (PA) inhibitors, including Baloxavir acid (BXA) derived from a recently FDA-approved drug, Baloxavir marboxil (BXM), suggesting that the banyangvirus endonuclease domain is a major therapeutic target that can guide the development of broad-spectrum antivirals against sNSVs.…”
Section: In Briefmentioning
confidence: 99%
“…This motif defines this family of ENs, and can be found in the amino terminus of near all sNSV L proteins with the notable exception of nairovirus, including Crimean Congo Hemorrhagic Fever Virus (CCHFV), which after the EN motif have an additional extension of ≈600 aa at N-terminus harbouring the OTU domain (see below). Additional structures of cap-snatching ENs were reported for hantaviruses and Lassa virus (Fernández-García et al, 2016;Reguera et al, 2016b;Wallat et al, 2014), which together with Orthomyxoviridae family ENs (Dias et al, 2009;Guilligay et al, 2014;Yuan et al, 2009) have generated a broad perspective of their structure and function. The PD.…”
Section: Structure Of L Proteinsmentioning
confidence: 99%
“…N protein binds to the mRNA caps and protects capped mRNA fragments up to 180 nucleotides inside P-bodies that were efficiently processed by an unknown mechanism to generate 14-nucleotide-long RNA primers with a 3= G residue (18). Since bacterially expressed and purified endonuclease domain nonspecifically cleaved the RNA in vitro (11), it was not clear how capped primers of appropriate length and defined 3= terminus are generated during cap snatching. Our recently published results demonstrating the interaction between the N protein and C-terminal uncharacterized domain of RdRp provided insights about a possible mechanism for the generation of capped primers of appropriate length and defined 3= terminus from the protected capped mRNA fragments inside P-bodies.…”
Section: Resultsmentioning
confidence: 99%
“…The structure-based sequence alignments revealed that the cap-snatching endonuclease domain almost certainly exists at the N terminus of almost all known negative-strand and capsnatching segmented RNA viruses, including bunyaviruses, tentiviruses, arenaviruses, and orthomyxoviruses. The X-ray crystal structures of cap-snatching endonuclease domain from La Crosse orthobunyavirus (LCV), Andes hantavirus, and influenza virus reveal a similar overall fold and two identical metal binding active sites (8,9,11,25). Interestingly, the purified N-terminal endonuclease domain from LCV, hantavirus, and influenza virus nonspecifically cleaved RNA in vitro, and the enzymatic activity was metal ion dependent (8,9,11,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation